Hubungan Pola Asuh Orang Tua terhadap Perkembangan Moral Siswa Kelas Tinggi Di SD Negeri Cimpon Desa Tirtosari Kecamatan Kretek Kabupaten Bantul Tahun Ajaran 2014/2015 - Khanif Maksum; Shofia Khusni Winasih (LITERASI (Jurnal Ilmu Pendidikan), 2017)
Shofia Khusni Winasih: "The Relationship between Parenting Paterns and Moral Development of Upper Grades Students at Cimpon State Elementary School Tirtosari Village, Kretek District, Bantul Regency in Academic Year of 2014-2015". Essay. Yogyakarta: Bachelor Program Madrasah Ibtidaiyah Teacher Education, ALMA ATA Islamic Higher Education, 2015.            This research is a survey research that takes sample from one population and uses questionnaire as the main data collection tool. The population in this study are 46 upper grades students and their parents Cimpon State Elementary School in Academic Year of 2014-2015. Samples are taken by using simple random sampling is which sample members of the population are taken randomly without any regard to the stratas in the population. Variables in this study consists of variable X (Parenting pattern from upper grades students’ parents) and variable Y (Moral Development the upper grades students). The data collection techniques used in this research are obsevation, questionnaires, interviews, and documentation. Meanwhile, questionnaire were taken by using likert scale instrument: Strongly Agree (SS), Agree (S), Neutral / Doubt (N), Disagree (TS), Strongly Disagree (STS).The results of this research shows that 3 parents (6.52%) used uthoritarian parenting patern and all of their children, three children (100%), showed less moral development. Parents who adopted democratic parenting were 43 parents (93.48%) and most of their children, 23 children (53.5%), showed adequate moral development and the rest of the children, 20 children (46.5%), showed good moral development. Most of the upper grades students showed adequate moral development (23 children or 50%); incontrast, children with less moral development were found as the smallest number (3 children or 6.5%).The result of Pearson correlation test obtained the value of X2 -0.380 and were significant at 0.009 (p-value <0.05). This means that there is a relationship between parental patterns to children moral development in upper grades students in Cimpon Elementary School, Tirtosari Village, Kretek District, Bantul Regency in Academic Year of 2014/2015. In other words, this research hypothesis can be proven or accepted.Keyword: Parenting Pattern, moral development.